(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Now a days, heart disease is one among the most complicated issues and globally many people Effected from this disease. A major obstacle to clinical data analyticsis the disease’s prediction. In time identification of disease is crucial to save patient, so health industry collect data from across world and transforms huge amounts of raw data into useful information. With the help of this useful information, we executed various machine learning algorithms to predict the heart disease